Clubhouse Model of Psychiatric Rehabilitation in China to Promote Recovery of People With Schizophrenia: A Systematic Review and Meta-Analysis - Yan, Haohao; Ding, Yudan; Guo, Wenbin (Frontiers in Psychiatry, 2021)
Background: Whether the clubhouse model of psychiatric rehabilitation is well implemented in China and whether patients with schizophrenia successfully achieve symptom remission and functional recovery through engaging in the clubhouse remain unclear. Methods: Seven electronic databases were searched for relevant articles from inception to April 21, 2021. Quality assessment, data synthesis, and subgroup analysis were performed on the included studies. Results: Seven randomized controlled studies with 682 participants were included in the present meta-analysis. The clubhouse model of psychiatric rehabilitation has a significant effect on promoting the remission of psychiatric symptoms, especially negative symptoms. However, it does not show a definite effect on promoting recovery of positive symptoms. The clubhouse model of psychiatric rehabilitation has a significant effect on promoting social functioning recovery, reducing the family burden, improving the quality of life, and promoting the remission of depressive and anxiety symptoms of patients with schizophrenia in China. Conclusions: Our findings suggest that the clubhouse model of psychiatric rehabilitation can promote the remission of symptoms and functional recovery of Chinese with schizophrenia. It may be suitable to address the urgent need for better mental health services in China.